MULOQOT SHAKLIDA TASVIR VA IFODA MUTANOSIBLIGI - Matyakupov, S. (SCIENCE and SOCIETY, 2022)
The article theoretically generalizes the nature of dialogue in poetry, the provision of clarity and conciseness in artistic speech, the interdependence of debate and attitude, the creative independence of expression in the context. It observes the connection between the technique of narration and the situation, the status of communication in the concept of poetic interpretation, nominative, semiotic and communicative functions in the formation of the image psyche, as well as methodological differences.